INCARCERATED INGUINAL HERNIAS IN CHILDREN - Polona Studen Pauletič (The Society for Children with Metabolic Disorders, 2020)
Introduction. Inguinal hernia is the most common condi-tion requiring surgical treatment in children. Incarceration describes a hernia that cannot be reduced by manipulation. Strangulation refers to vascular compromise of the contents of an incarcerated hernia and is, therefore, a surgical emergency. Strangulation can be avoided when incarceration is promptly recognised and treated. Methods. We performed a review of the literature on incarcerated inguinal hernia and performed statistical analysis of incarcerated inguinal hernias treated in the University Medical Centre Ljubljana in the last 5 years. Results. According to the literature, the incidence of incarcerated and irreducible inguinal hernia in children ranges between 0.9-3%. Between January 2015 and September 2019, in the University Medical Centre Ljubljana, 32 patients were treated for incarcerated hernia, with manual repositioning being successful in 12. In that period, 897 children underwent elective surgery for inguinal hernias. The incidence of incarcerated hernia in children in our centre was 2.1%. Conclusion. The incidence of incarcerated hernia in our institution is comparable to the published results. Children under the age of two years should be managed in centres with proper equipment and trained staff. It is of utmost importance to promptly recognise and treat a child with an incarcerated hernia by repositioning the hernia.